Drivers of food price in China: A heterogeneous panel SVAR approach. (4th January 2021) - Wu, Xiangjun; Xu, Juan
Abstract: In this paper, we examine the effects of shocks in agricultural output, production material price and production price on China's food price using panel data of 26 provinces for the period 2004 Q1–2015 Q4. Employing a heterogeneous panel structural vector autoregressive (SVAR) model, we identify the causal flows between the endogenous variables via directed acyclic graphs method. The empirical results from impulse response functions and variance decompositions suggest sizeable cross‐province variations. The main driving force of food price is the price inertia shock, rather than the agricultural output or the vertical chain of price transmission shocks. The findings support the view that price expectation is the key shifter of food price. Moreover, the shocks in the vertical chain of price transmission are only weakly linked to food price. Our findings are robust to an alternative panel SVAR model identified via Cholesky decomposition.